Measuring food price volatility - Traoré, Fousseini; Diop, Insa (International Food Policy Research Institute, 2021)
Over the past two decades, the prices of agricultural commodities have experienced large and unpredictable fluctuations that have attracted the attention of researchers, policymakers and the media to better understand the mechanisms that govern this phenomenon. It is therefore important to acquire basic tools to assess the level of price volatility to warn of abnormal movements. The main objective of this technical is to provide an overview of this literature in constant evolution, and tools for measuring food price volatility. The tools developed in this technical help understand the complexity of measuring volatility and the caution required in their use. Thus, the application of these tools requires their adaptation to the nature of the data generating process and the use of appropriate tests and criteria in order to choose the best approach.